Coronavirus disease 2019 (COVID-19) pandemic, central-line–associated bloodstream infection (CLABSI), and catheter-associated urinary tract infection (CAUTI): The urgent need to refocus on hardwiring prevention efforts. (19th January 2022) - Fakih, Mohamad G.; Bufalino, Angelo; Sturm, Lisa; Huang, Ren-Huai; Ottenbacher, Allison; Saake, Karl; Winegar, Angela; Fogel, Richard; Cacchione, Joseph
Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has had a considerable impact on US hospitalizations, affecting processes and patient population. Objective: To evaluate the impact of COVID-19 pandemic on central-line–associated bloodstream infections (CLABSIs) and catheter associated urinary tract infections (CAUTIs) in hospitals. Methods: We performed a retrospective study of CLABSIs and CAUTIs in 78 US 12 months before COVID-19 and 6 months during COVID-19 pandemic. Results: During the 2 study periods, there were 795, 022 central-line days and 817, 267 urinary catheter days. Compared to the period before the COVID-19 pandemic, CLABSI rates increased by 51.0% during the pandemic period from 0.56 to 0.85 per 1, 000 line days ( P < .001) and by 62.9% from 1.00 to 1.64 per 10, 000 patient days ( P < .001). Hospitals with monthly COVID-19 patients representing >10% of admissions had a National Health Safety Network (NHSN) device standardized infection ratio for CLABSI that was 2.38 times higher than hospitals with <5% prevalence during the pandemic period ( P = .004). Coagulase-negative Staphylococcus CLABSIs increased by 130% from 0.07 to 0.17 events per 1, 000 line days ( P < .001), and Candida spp by 56.9% from 0.14 to 0.21 per 1, 000 line days ( P = .01). In contrast, no significant changes were identified for CAUTI (0.86 vs 0.77 per 1, 000 catheter days; P = .19). Conclusions: The COVID-19 pandemic was associated with substantial increases in CLABSIs but not CAUTIs. Our findings underscore the importance of hardwiring processes for optimal line care and regular feedback on performance to maintain a safe environment.